Characteristics of Maxillofacial Trauma Cases Before and During the Pandemic: A Rapid Review - Hidayah, Meta Tria; Sjamsudin, Endang; Yuza, Abel Tasman (Newinera Publisher, 2025)
Maxillofacial trauma refers to injuries affecting the facial region and its surrounding tissues, involving both hard and soft tissue structures. When accompanied by head trauma, such injuries can be life-threatening, highlighting the critical need for prompt medical intervention. The emergence of SARS-CoV-2 in December 2019 prompted the World Health Organization (WHO) to recommend widespread social restrictions, significantly altering various aspects of life, including the patterns of maxillofacial trauma. This study aims to provide an overview of the characteristics of maxillofacial trauma before and during the COVID-19 pandemic. This study employs a rapid review methodology following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data were retrieved from Scopus, ScienceDirect, and PubMed databases using specific keywords: for the pre-pandemic period — (maxillofacial trauma* OR maxillofacial injuries) AND (incidence OR etiology OR type); and for the pandemic period — (maxillofacial trauma* OR maxillofacial injuries) AND (incidence OR etiology OR type) AND (COVID-19 OR COVID 19 OR coronavirus OR SARS-CoV-2). A total of 15 articles met the inclusion criteria and were analyzed qualitatively. Prior to the pandemic, 15 etiological factors were identified, with road traffic accidents, falls, and interpersonal violence being the most common. The most prevalent types of trauma were orbital, mandibular, and zygomaticomaxillary complex (ZMC) injuries. During the pandemic, a decrease in reported cases was observed, along with fewer recorded etiological factors. Mandibular trauma emerged as the most frequently reported type, followed by orbital and ZMC trauma.